2017
DOI: 10.1080/10245332.2017.1396056
|View full text |Cite
|
Sign up to set email alerts
|

Gestational age and childhood leukemia: A meta-analysis of epidemiologic studies

Abstract: Our results suggest that both preterm and postterm infants have an elevated risk of developing AML. In addition, postterm birth increased the risk of childhood leukemia and ALL in cohort studies. However, more studies are warranted to validate these results and explore the biologic mechanisms underlying these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
1
13
1
Order By: Relevance
“…We also found the risk of AML to be increased, again confirming results previously published. 26,31 Yet, and unlike previous studies, we found a strong association between preterm birth and later diagnosis of a germ cell tumor or retinoblastoma. For hepatic tumors, we were hampered by the low numbers with only three cases in our preterm population, but the OR was suggestive of an elevated risk.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We also found the risk of AML to be increased, again confirming results previously published. 26,31 Yet, and unlike previous studies, we found a strong association between preterm birth and later diagnosis of a germ cell tumor or retinoblastoma. For hepatic tumors, we were hampered by the low numbers with only three cases in our preterm population, but the OR was suggestive of an elevated risk.…”
Section: Discussioncontrasting
confidence: 99%
“…20,21 The risk of developing childhood cancer after having been born preterm has been studied previously. [22][23][24][25][26][27][28] Certain subtypes of childhood cancer, that is, hepatoblastoma [27][28][29][30] and acute myeloid leukemia (AML), 26,31 have been found to be associated with preterm birth. The possible association between other childhood cancers and preterm birth, however, remains inconclusive.…”
mentioning
confidence: 99%
“…In the functional analyses, we observed significant enrichment for several GO terms related to embryonic development, regulation of process and immune system development. The pathway analyses identified a subset of these genes linked to diseases also associated with low gestational age, for example asthma [83], inflammatory bowel disease [84], type I/II diabetes [85] and cancer (leukaemia) [86]. Importantly, genes annotated to CpGs found stable across childhood also showed enrichment for infection-and immune-related conditions.…”
Section: Discussionmentioning
confidence: 99%
“…94 This can be explained by the fact that preterm babies have immature lungs and other vital organs, which exposed them to respiratory problems including infections, facing difficulty to adapt the extra-uterine life. Premature newborns are at risk for death during the neonatal period 21 due to higher rates of associated neonatal morbidities such as neonatal sepsis, 95 neonatal near miss and foetal malformations, 96 leukaemia, 97 retinopathy of prematurity, 12,21 respiratory distress, feed intolerance and jaundice 98 and neonatal sepsis. [98][99][100] A recent study conducted in Ethiopia also showed the highest rate of preterm mortality was attributed to respiratory problems distress syndrome (45%), infections (30%) and asphyxia (14%).…”
Section: Discussionmentioning
confidence: 99%